THE FINANCIAL CRIME IN HELLAS AND ITS COMBATING BY THE HELLENIC LAW ENFORCEMENT AGENCIES. THE CONTRIBUTION OF THE EU ORGANIZATIONS OF EUROPOL AND EUROJUST - Tryfon Korontzis (European Scientific Journal, ESJ, 2014)
As is being known Hellas is in a crucial turning point of its modern history, as the economic policies during the last three decades have lead the economy to bankruptcy threshold. But overall crisis that Hellas faces in social and political level as a result of the economic crisis but also as a result of numbers structural problems which have been developed over the last thirty years in the country, repeatedly raise in the forefront a request – which occupies the majority of the citizens: the prosecution of financial crime. The reasons for this are obvious and fully understood. Key financial issues for Hellas as many surveys have shown constitute bribery, corruption, tax evasion, tax opacity but also the confidence lack to the authorities. To these should be added and the demerit of Hellenic citizens for the Hellenic political leadership class. With a financial control mechanism that cannot function adequately and effectively, the deficits to remain, unemployment is increased and the black economy to be in soaring, citizens expect that control mechanisms could lead on the revenue increased for the State, but also through effective action by the competent authorities in this section, to be discouraged citizens as far as concerns the law-breaking that demonstrate in areas related to financial activities.